What Constitutes Sufficient Evidence for Case Formulation–Driven CBT for Psychosis? Cumulative Meta-analysis of the Effect on Hallucinations and Delusions. (27th March 2020) - Turner, David T; Burger, Simone; Smit, Filip; Valmaggia, Lucia R; van der Gaag, Mark
Abstract: Objective: Following 2 decades of research on cognitive behavioral therapy for psychosis (CBTp), it is relevant to consider at which point the evidence base is considered sufficient . We completed a cumulative meta-analysis to assess the sufficiency and stability of the evidence base for hallucinations and delusions. Method: We updated the systematic search from our previous meta-analytic review from August 2013 until December 2019. We identified 20 new randomized controlled trials (RCTs) resulting in inclusion of 35 RCTs comparing CBTp with treatment-as-usual (TAU) or active controls (AC). We analyzed data from participants with psychosis ( N = 2407) over 75 conventional meta-analytic comparisons. We completed cumulative meta-analyses (including fail-safe ratios) for key comparisons. Publication bias, heterogeneity, and risk of bias were examined. Results: Cumulative meta-analyses demonstrated sufficiency and stability of evidence for hallucinations and delusions. The fail-safe ratio demonstrated that the evidence base was sufficient in 2016 for hallucinations and 2015 for delusions. In conventional meta-analyses, CBTp was superior for hallucinations ( g = 0.34, P < .01) and delusions ( g = 0.37, P < .01) when compared with any control. Compared with TAU, CBTp demonstrated superiority for hallucinations ( g = 0.34, P < .01) and delusions ( g = 0.37, P < .01). Compared with AC, CBT was superior for hallucinations ( g = 0.34, P < .01), but not for delusions although this comparison was underpowered. Sensitivity analyses for case formulation, primary outcome focus, and risk of bias demonstrated increases in effect magnitude for hallucinations. Conclusions: The evidence base for the effect of CBTp on hallucinations and delusions demonstrates sufficiency and stability across comparisons, suggesting limited value of new trials evaluating generic CBTp.